Crime Prevention Through Environmental Design for Low-Income Residents (B40) in Sabah, Malaysia - Alias, Zuraini; Mohamed Mohan, Noor Malinda; Abdol Ghani, Mohd Reza; Saad, Mazni; Abdullah, Mokhtar (2023)
Safety, facilities, and environment are known to be among the core factors that influence the Quality of Life (QoL)of neighbourhood communities. This study evaluates the low-income residents’ (B40)QoL and seeks to clarify whether People’s Housing Program Environment(PPRE)and Crime Prevention through Environmental Design (CPTED)can be used collaboratively to improve the QoL of the People’s Housing Project(PPR)communities. This study hypothesizes that implementing CPTED is one of the strategies that may enhance the feeling of safety in residential environments. This study utiliseda quantitative cross-sectional design to collect data from 150 PPR residents. The PLS-SEM method reveals that a good PPRE has a significant impact on the residents’QoL. While the study’s focus is primarily on the expected impact of CPTED on residents’QoL, the main finding suggests that CPTED can have a large impact on QoL on its own, but not as a mediator between PPRE and QoL. Community relationship, maintenance, natural surveillance, legitimate activity support, and target hardening were the five most important CPTED constructs. However, results did not support territorial reinforcement and natural access control as CPTED facilitators. This information is necessary for developing effective CPTED in housing policies that may improve PPR residential well-being.